Sistem Penentu Suhu Dan Kelembaban Incubator Telur Unggas Berdasarkan Berat Dan Warna Telur Menggunakan Metode Fuzzy - Moh. Zainur Rodhi; Dahnial Syauqy; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Egg hatching machine is one innovation in technology that is proven to increase production results in poultry farming. But the existing egg hatchery machine is considered still less efficient, because in terms of functionality, one unit of egg hatchery machine only serves to incubate just one particular egg species and can not be used to incubate different egg species. As the result based on this problem, come an idea for designing temperature and humidity control sistems using the weight and color of poultry eggs on poultry egg Incubator for chicken egg, duck egg and quail egg. This sistem is created using a load cell sensor to detect the egg weight, color sensor TCS3200 to detect egg color, DHT11 sensor to detect air temperature and humidity and arduino uno as the data processor of the sensor. The process of detecting eggs done by using fuzzy logic. This sistem is able to adjust the temperature and humidity values ​​in the Incubator automatically according to the egg species detected. Adjust the temperature value using a bulb lamp which functions as a heating, while for humidity use humidifier which functions to increase the value of air humidity. From the results of fuzzy logic testing obtained error percentage of 0.001%, and aktuator conditions to adjust the temperature and humidity values is in compliance with the required conditions.